Prevalence and clinical manifestations of patients with psoriasis in RSUP Sanglah from 2017 to 2018 - Daarshawnee Segar; IGAA Praharsini; IGAA Elis Indira (DiscoverSys Inc., 2019)
Background: Psoriasis is a complex, multifactorial, inflammatory, chronic autoimmune disorder that changes the life cycle of skin cells. In countries around the world, the prevalence of psoriasis ranges from 0.09% to 11.43%.Objective: This study aims to determine the prevalence and clinical manifestations of patients with psoriasis in RSUP Sanglah Denpasar from the year 2017 to 2018.Method: The study used is a descriptive retrospective study design using total sampling with142 samples recorded.Results: The prevalence of psoriasis was 0.603% in 2017 and 0.708% in 2018. Between 2017 till 2018, a total of 142 patients reported having psoriasis with 73 patients (51.4%) in 2017 and 69 patients (48.6%) in 2018. The cases were dominated by males with 90 patients (63.4%) and females with 52 (36.6%) for both the years. Psoriasis patients between the ages of 36-45 years were reported the most with a proportion of 23.2%. The least number of patients were reported below the age of 5 years. There was a total of 63(44.4%) patients diagnosed with psoriasis vulgaris which is also the most common type of psoriasis case found in Sanglah. The least number of patients were psoriasis inverse and erythrodermic with 4(2.8%) patients each.Conclusion: The clinical manifestations used to diagnose psoriasis were red sharp boundaries erythematous plaque, covered with silver or scaly white squamae and geographic skin lesion. This clinical finding was used for almost all psoriasis diagnosis.